Contrast-induced Nephropathy: Incidence and Reversibility in Patients Undergoing High-risk Percutaneous Coronary Intervention - Bharat Singh Sambyal; Vishal Kansal; Akshay Kumar Nayak; Prabhat Chauhan; Kavya Jeldi (Journal of Marine Medical Society)
Introduction: There is a paucity of data regarding contrast-induced nephropathy (CIN) in patients undergoing percutaneous coronary intervention (PCI) from this part of the world. The present study was thus planned to find the incidence and reversibility of CIN in patients undergoing high-risk PCI. Materials and Methods: A hospital-based observational study was conducted at the department of cardiology in a tertiary care hospital. The study included 50 consecutive cases undergoing high-risk PCI at the cardiac catheterization laboratory. CIN is characterized as either a relative increase in serum creatinine (S. Cr) of 25% or more or an absolute increase of 0.5 mg/dL or more, occurring within 48 h of exposure to contrast media. This is under the assumption that there are no other factors contributing to the increase in S. Cr. Results: The incidence of CIN in cases undergoing high-risk percutaneous interventions was 18% in the present study. On regression analysis, age above 70 years, hypertension and diabetes were identified as significant predictors of the development of CIN in patients undergoing cardiac procedures in the cardiac catheterization laboratory (P < 0.01). All the cases of CIN had a self-limiting course, and none of the cases required renal replacement therapy. Conclusion: CIN affects one out of every five to six cases undergoing high-risk PCI; however, almost all cases are reversible. Patients with preexisting comorbidities such as diabetes and hypertension have a significantly increased risk of development of CIN.